2004
DOI: 10.1177/0363546503262174
|View full text |Cite
|
Sign up to set email alerts
|

Stress Fracture Nonunion at the Base of the Second Metatarsal in a Ballet Dancer

Abstract: Stress fractures are defined as spontaneous fractures of normal bone that are the result of repetitive stresses that are themselves harmless. 1 Although the metatarsal shaft is the most common location of a stress fracture in the general population, the base of the second metatarsal is by far the most common site in ballet dancers. Few series published in the orthopaedic literature report a quick recovery of this fracture after conservative treatment, and cases of nonunion have not been previously reported. 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 7 publications
0
29
0
1
Order By: Relevance
“…4 Several authors 3,4,[13][14][15] have reported that classical ballet injuries have the highest occurrence of dance injuries. Knowledge on the causes of injury in dancers is important to the understanding of how such injuries occur and the adoption of preventive measures aimed at maintaining the health of the dancers.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several authors 3,4,[13][14][15] have reported that classical ballet injuries have the highest occurrence of dance injuries. Knowledge on the causes of injury in dancers is important to the understanding of how such injuries occur and the adoption of preventive measures aimed at maintaining the health of the dancers.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographs may be normal for the first 2–3 weeks after stress fracture development 1. MRI had been suggested necessary to differentiate a stress fracture from synovitis of the Lisfranc joint6; however, they both require the same conservative management. Currently, MRI is not considered essential in the diagnosis of a metatarsal stress fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MRI is not considered essential in the diagnosis of a metatarsal stress fracture. CT may also play a part when identifying the exact location of the stress fracture1 and for assessment of healing and diagnosing non-union 6…”
Section: Discussionmentioning
confidence: 99%
“…They are common injuries in runners, military recruits, ballet dancers, and basketball players, and most patients will report a recent increase in training. [1][2][3][4][5][6][7][8]10,13,20,22,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Forefoot pain with weight bearing, inability to toe walk, point tenderness, and swelling are present on exam. [1][2][3][4][5][6][7][8]10,13,20,22,[41][42][43][44][45][46][47][48]…”
Section: Metatarsalmentioning
confidence: 99%
“…41,43 The insidious onset of vague midfoot pain is often overlooked or misdiagnosed. 41,43,49,[51][52][53]56 The second and third metatarsals are most affected.…”
Section: Second and Third Metatarsal Basementioning
confidence: 99%